Tea‐Bag‐Like Polymer Nanoreactors Filled with Gold Nanoparticles1. Issue 19 (2nd April 2014) - Mitschang, Fabian; Schmalz, Holger; Agarwal, Seema; Greiner, Andreas
Abstract Gold‐containing polymer nanotubes, which showed both catalytic activity and resistance to leaching, were prepared by the "tubes by fiber templates" (TUFT) process. For this purpose, electrospun polymer nonwovens with incorporated poly(L‐lactide)‐stabilized gold nanoparticles were coated with poly(p‐xylylene) by the chemical vapor deposition process, and then the inner fiber templates were removed. The resulting polymer tubes carried encapsulated gold nanoparticles which were shown to be immobilized and featured pronounced catalytic activity towards the hydrolytic oxidation of dimethylphenylsilane and the alcoholysis of dimethylphenylsilane with n‐butanol. The macroscopic nonwovens could be used as tea‐bag‐like catalyst systems and showed excellent reusability.